The Goldbach Conjecture With Summands In Arithmetic Progressions - Salmensuu Juho (OXFORD UNIV PRESS, 2022)
We prove that, for almost all r <= N-1/2/log(O(1)) N, for any given b(1) (mod r) with (b(1), r) = 1, and for almost all b(2) (mod r) with (b(2), r) = 1, we have that almost all natural numbers 2(n) <= N with 2n b(1) + b(2) (mod r) can be written as the sum of two prime numbers 2n = p(1) + p(2), where p(1) b(1) (mod r) and p(2) b(2) (mod r) . This improves the previous result which required r <= N-1/3/log(O(1)) N instead of r <= N-1/2/log(O(1))N. We also improve some other results concerning variations of the problem.